IMPROVING STUDENTS’ SPEAKING SKILLS WITH ACTION LEARNING STRATEGY AT EIGHTH GRADE OF JUNIOR HIGH SCHOOL (A Classroom Action Research at Eight Grade Students of SMP N 01 Kota Bengkulu) - Dorea Afrilia Wulandari; Kasmaini Kasmaini; Indah Damayanti (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2021)
This research aimed to see the improvement of students’ speaking skill in english lesson by using action learning strategy at eighth grade. The participants of this research were 32 students form VIII.6 class consisting on 15 male and 17 female. This research used Classroom Action Research (CAR). The data were obtained through the observation and speaking test. To determine students who are successful in improving speaking skills based on the KKM (Minimum Completeness Criteria), which is 80. To analysis the data, the researcher used two steps, namely scoring students speaking skills use quantitative data and calculating the students’ score. The results of this study showed an increase in students' speaking ability. The results of this research indicate an improve in students' speaking ability. Students who experienced an increase in speaking skills in the preliminary data was 62.5%, or 20 students, the cycle I was 75% or 24 students and the cycle II was 84.375% or 27 students. While students who did not succeed in the preliminary data was 37.5% or 12 students, the cycle I was 25% or 8 students and the  cycle II was 15.675% or 5 students. Based on the results of interviews conducted by researchers to several samples of students, several factors were found that were able to improve students' speaking skills. These factors were the comfort that students get while studying, giving reward points to attract students' interest and teachers applied some learning tricks  to attract students' attention while studying.